INCLUSION OF CHILDREN AND TEENS WITH SPECIAL NEEDS: WHAT THE TEACHERS THINK (Fiep Bulletin - online, 2015)
For the process of teaching and learning to be successful several factors must be considered and planned. The inclusion of people with special needs in mainstream schools is reality and it is up to the teacher-conductor one of the main roles for inclusion to occur satisfactorily. This field study aimed to know the views of teachers on the inclusion of students with special needs in school; identify the type of access that these students have the common learning; meet the offer of educational services and specialize check for problems by the teacher in performing activities with these students. After conducting literature survey, the questionnaire for teachers of Basic Education expose your opinion on the subject in question was applied. It was found that the teacher is aware of their important role in the inclusion process, but the lack of real knowledge about the types of learning disorders and the number of students in class are the factors that most contribute to the student's attendance does not is realized in the most appropriate way to your need.
Keywords: Learning disorders; social and educational inclusion; education.